If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(2x + 4) = 5(3x + -4) Reorder the terms: 6 + -1(4 + 2x) = 5(3x + -4) 6 + (4 * -1 + 2x * -1) = 5(3x + -4) 6 + (-4 + -2x) = 5(3x + -4) Combine like terms: 6 + -4 = 2 2 + -2x = 5(3x + -4) Reorder the terms: 2 + -2x = 5(-4 + 3x) 2 + -2x = (-4 * 5 + 3x * 5) 2 + -2x = (-20 + 15x) Solving 2 + -2x = -20 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 2 + -2x + -15x = -20 + 15x + -15x Combine like terms: -2x + -15x = -17x 2 + -17x = -20 + 15x + -15x Combine like terms: 15x + -15x = 0 2 + -17x = -20 + 0 2 + -17x = -20 Add '-2' to each side of the equation. 2 + -2 + -17x = -20 + -2 Combine like terms: 2 + -2 = 0 0 + -17x = -20 + -2 -17x = -20 + -2 Combine like terms: -20 + -2 = -22 -17x = -22 Divide each side by '-17'. x = 1.294117647 Simplifying x = 1.294117647
| n-10=-20 | | -2+k=-2 | | -7+d=-1 | | n/2=-1 | | 7+a=-3 | | n+2=-8 | | -1/2u+6+4=6/u+3 | | x+4x+4+6x+9=16 | | 9=d+9 | | -11=m-5 | | n/7=4 | | 34+(.08)x=91-(.02)x | | 9.5/2.5 | | b-8=-19 | | 11=k+2 | | t-2=-5 | | 8+d=3 | | 4k=-16 | | -3m=-18 | | k/-6=-2 | | w-2=6 | | k-9=-9 | | 5=k+4 | | f/4=11 | | -1+b=3 | | (.05)x+24=36 | | 6(1+3m)=-8(2u-4)-9 | | 17=a+8 | | d+10=13 | | 8=b+5 | | 1+w=5 | | x+4x+4+6x+9=4 |